The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.pbb.2012.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Strain differences in delay discounting between Lewis and Fischer 344 rats at baseline and following acute and chronic administration of d-amphetamine

Abstract: Stimulant drugs have been shown either to increase or decrease rates of delay discounting (impulsive choice). These mixed findings may result from genetic, neurochemical, or environmental factors. Lewis (LEW) and Fischer 344 (F344) rats have neurochemical and behavioral differences that may be relevant to delay discounting and were used to examine effects of acute and chronic administration of d-amphetamine (d-AMP) on impulsive choice using a within-session delay-discounting procedure. Male LEW (n=8) and F344 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 45 publications
6
57
1
Order By: Relevance
“…It could be said that in adjusting to the transition from the ascending to the descending presentation order of delays, the LEWs did so more rapidly than the F344s, choosing the LL lever at higher proportions during most delays to LLR. This result is in dispute with previous findings (Anderson & Diller, 2010;Anderson & Woolverton, 2005;Huskinson et al, 2012;Madden et al, 2008;Stein et al, 2012) that showed more impulsivity in the LEWs; the assertion that the LEWs choose more impulsively than the F344s is not supported by the present study, challenging this strain difference and confirming that it may be due to procedural issues (Stein et al, 2012) and the analytical tools used to characterize impulsive choice (Madden & Johnson, 2010).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It could be said that in adjusting to the transition from the ascending to the descending presentation order of delays, the LEWs did so more rapidly than the F344s, choosing the LL lever at higher proportions during most delays to LLR. This result is in dispute with previous findings (Anderson & Diller, 2010;Anderson & Woolverton, 2005;Huskinson et al, 2012;Madden et al, 2008;Stein et al, 2012) that showed more impulsivity in the LEWs; the assertion that the LEWs choose more impulsively than the F344s is not supported by the present study, challenging this strain difference and confirming that it may be due to procedural issues (Stein et al, 2012) and the analytical tools used to characterize impulsive choice (Madden & Johnson, 2010).…”
Section: Discussioncontrasting
confidence: 99%
“…In conclusion, through the present study we investigated both the acquisition and maintenance of the impulsive behavior of LEWs and F344s, and found more dynamic changes in choice characterizing impulsivity than those previously reported in studies using a rapid-redetermination assessment of indifference points (e.g., Stein et al, 2012;Wilhelm & Mitchell, 2009) and steady-state procedures (e.g., Anderson & Diller, 2010;Anderson & Woolverton, 2005;Huskinson et al, 2012;Madden et al, 2008;Stein et al, 2012). Consistent with findings obtained in nonhuman (Fox et al, 2008) and human (Robles & Vargas, 2007Robles et al, 2009) animals, we found that the presentation order of delays to the LLR is important in determining the discounting rate (k in Eq.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…While much of our work has examined impulsive choice in outbred populations, we have also assessed impulsive choice in inbred strains of rats that are potential animal models of ADHD (Garcia & Kirkpatrick, 2013). The spontaneously hypertensive (SHR) and Lewis strains have been derived from their respective control strains, the Wistar Kyotos (WKY) and Wistars, and both have been reported to demonstrate possible markers of increased impulsive choice in previous studies (Anderson & Diller, 2010;Anderson & Woolverton, 2005;Bizot et al, 2007;Fox, Hand, & Reilly, 2008;García-Lecumberri et al, 2010;Hand, Fox, & Reilly, 2009;Huskinson, Krebs, & Anderson, 2012;Madden, Smith, Brewer, Pinkston, & Johnson, 2008;Stein, Pinkston, Brewer, Francisco, & Madden, 2012). Garcia and Kirkpatrick (2013) sought to potentially isolate the source of impulsive choice behaviors to either deficits in delay or magnitude sensitivity by delivery of two different impulsive choice tasks modeled after previous research (Galtress & Kirkpatrick, 2010;Roesch, Takahashi, Gugsa, Bissonette, & Schoenbaum, 2007).…”
Section: Moderating Impulsive Choicementioning
confidence: 99%